Cardiac Surgery 2020 Reviewed - Doenst, Torsten; Caldonazo, Tulio; Schneider, Ulrich; Moschovas, Alexandros; Tkebuchava, Sophie; Safarov, Rauf; Diab, Mahmoud; Färber, Gloria; Kirov, Hristo (The Thoracic and Cardiovascular Surgeon, 2021)
In 2020, nearly 30,000 published references appeared in the PubMed for the search term “cardiac surgery.” While SARS-CoV-2 affected the number of surgical procedures, it did not affect outcomes reporting. Using the PRISMA approach, we selected relevant publications and prepared a results-oriented summary. We reviewed primarily the fields of coronary and conventional valve surgery and their overlap with interventional alternatives. The coronary field started with a discussion on trial data value and their interpretation. Registry comparisons of coronary artery bypass surgery (CABG) and percutaneous coronary intervention confirmed outcomes for severe coronary artery disease and advanced comorbidities with CABG. Multiple arterial grafting was best. In aortic valve surgery, meta-analyses of randomized trials report that transcatheter aortic valve implantation may provide a short-term advantage but long-term survival may be better with classic aortic valve replacement (AVR). Minimally invasive AVR and decellularized homografts emerged as hopeful techniques. In mitral and tricuspid valve surgery, excellent perioperative and long-term outcomes were presented for structural mitral regurgitation. For both, coronary and valve surgery, outcomes are strongly dependent on surgeon expertise. Kidney disease increases perioperative risk, but does not limit the surgical treatment effect. Finally, a cursory look is thrown on aortic, transplant, and assist-device surgery with a glimpse into the current stand of xenotransplantation. As in recent years, this article summarizes publications perceived as important by us. It does not expect to be complete and cannot be free of individual interpretation. We aimed to provide up-to-date information for decision-making and patient information.
Keywords: coronary artery bypass surgery; CABG; aortic valve; mitral valve surgery; tricuspid valve; transplantation; heart